Comparison of The Sensitivity of Generic and Branded Ciprofloxacin Antibiotics Against Salmonella Typhi - Wulandari, Mustika; Arsal, Andi Sitti Fahirah; Sodiqah, Yani; Fattah, Nurfachanti; Hadele, Amrizal Muchtar (Faculty of Medicine, Universitas Tadulako, 2025)
Background. Salmonella typhi is the leading cause of typhoid fever, a gastrointestinal infection that resulted in about 9 million cases and 110,000 deaths globally in 2019. One of the drugs that is currently often used in the treatment of this disease is ciprofloxacin. Over time, more and more bacteria are experiencing drug resistance, including to these drugs. In addition, many patients also doubt the quality of generic ciprofloxacin drugs because they are cheaper than branded drugs. In fact, the Regulation of the Minister of Health No. HK.02.02/MENKES/068/I/2010 requires the use of generic drugs in government health facilities. Primary Objective: This study aimed to see and compare the sensitivity of generic and branded ciprofloxacin antibiotics in inhibiting Salmonella typhi. Methodology: This study was an antibiotic sensitivity test by the agar diffusion method (Kirby Bauer). Results: The results showed that one generic ciprofloxacin and seven branded classes still had sensitive inhibitory power and there was no significant difference between the generic and branded groups. Conclusions: There was no significant difference between generic and branded antibiotics between generic and branded antibiotics ciprofloxacin against Salmonella typhi.